PERAN RELAWAN DEMOKRASI KOMISI PEMILIHAN UMUM DALAM MENINGKATKAN PARTISIPASI POLITIK MASYARAKAT KOTA SURABAYA PADA PILWALI 2020 - Nurlaily, Ruwinda Ayu Dwi (Paradigma, 2022)
The Democracy Volunteers formed by the Election Commission is a social movement aimed at mobilizing voters to be active in the election stage. To achieve the target level of community participation that has been set in the National Medium-Term Development Plan (RPJMN) of 77.5% and face the challenge that the 2020 Simultaneous Elections are held in the midst of the Covid-19 virus pandemic, KPU Surabaya City formed a democracy volunteer program that became kpu’s partner in carrying out the agenda of socialization and voter education based in the city of Surabaya. This research uses qualitative methods with a perspective on the theory of Social Action by Max Weber. The results of this study show that the Democracy Volunteers formed by the Surabaya City KPU in PILWALI 2020 have not performed their role optimally because democracy volunteers have not been able to build public awareness and volunteerism of the people of the City of Surabaya to vote for PILWALI 2020. This is because not all democratic volunteer bases deliver materials that can build public awareness. Democracy volunteers are focused only on delivering election times, introducing candidates’ spouses, and voting procedures properly. Thus, this can be one of the factors that the increase in the number of community participation in PILWALI 2020 has not increased significantly. The socialization strategy carried out by KPU Surabaya City democracy volunteers is different in each base including door to door, cooperation with organizations, online, simulations, discussions to participate in citizen forums.